Light guidance film for bifacial photovoltaic modules. (January 2022) - Zauner, Markus; Muehleisen, Wolfgang; Holzmann, Dominik; Baumgart, Marcus; Oreski, Gernot; Feldbacher, Sonja; Feichtner, Markus; Nemitz, Wolfgang; Leiner, Claude; Sommer, Christian; Reil, Frank
Abstract: To improve the efficiency of bifacial photovoltaic modules, the idea of light deflection was addressed. A thin film with an intended structure was applied in the space between the cells. Due to the selected structural geometry, unused light is specifically redirected to the solar cell and can be absorbed by it and converted into additional current. The effect of the light-directing film was both simulated and measured. Single PV modules without and with commercial structured films or white back sheet were measured to evaluate the results The expected gain of up to 11% from the simulation could not be achieved by measurement, by reaching about 3%. Highlights: Simulations demonstrated that an additional gain of up to 11% can be achieved. Suitable materials for film and adhesive were evaluated. Using the roll produced with laser ablation, the structured film could be created. The produced films could be used for different applications depending on the light guidance.